Potential Importance of Early Focal Radiotherapy Following Gross Total Resection for Long-Term Survival in Children With Embryonal Tumors With Multilayered Rosettes - Mayr, Lisa; Gojo, Johannes; Peyrl, Andreas; Azizi, Amedeo A.; Stepien, Natalia M.; Pletschko, Thomas; Czech, Thomas; Dorfer, Christian; Lambo, Sander; Dieckmann, Karin; Haberler, Christine; Kool, Marcel; et al. (Frontiers in Oncology, 2020)
Embryonal tumor with multilayered rosettes (ETMR) is a rare, aggressive embryonal central nervous system tumor characterized by LIN28A expression and alterations in the C19MC locus. ETMRs predominantly occur in young children, have a dismal prognosis, and no definitive treatment guidelines have been established. We report on nine consecutive patients and review the role of initiation/timing of radiotherapy on survival. Between 2006 and 2018, nine patients were diagnosed with ETMR. Diagnosis was confirmed histopathologically, immunohistochemically and molecularly. Median age was 25 months (5-38). Location was supratentorial in five, pineal in three, brainstem in one. Seven patients had a gross total resection, one a partial resection and one a biopsy at initial diagnosis. Chemotherapy augmented with intrathecal therapy started a median of 10 days (7-20) after surgery. Only two patients who after gross total resection received radiotherapy very early on (six weeks after diagnosis) are alive and in complete remission 56 and 50 months after diagnosis. All remaining patients for whom radiotherapy was deferred until the end of chemotherapy recurred, albeit none with leptomeningeal disease. A search of the literature identified 228 patients with ETMR. Including our patients only 26 (11%) of 237 patients survived >36 months with no evidence of disease at last follow-up. All but two long-term (>36 months) survivors received radiotherapy, ten of whom early on following GTR. Gross total resection followed by early focal radiotherapy and intrathecal therapy to prevent leptomeningeal disease are potentially important to improve survival of ETMR in the absence of effective targeted therapies.